Semana Santa online? Modos de presença da Igreja Católica na pandemia - Rodrigues, Arnaldo; Zuque da Fonseca, Gilliard; Alves dos Santos, Rafael Alberto (E|C, 2021)
The validity of following Mass on TV and radio has been a matter of debate among theologians from the beginning. Catholic tradition considers the communal aspect of faith as essential, as is the reception of the sacraments in person. Throughout history, masses offered by the media have only been available to the faithful who are unable to be physically present in church (hospitalised, imprisoned, etc.). The outbreak of the pandemic broke the regularity of face-to-face celebrations. The present study aims to deduce the strategies of occupation of the digital space by the Church during this period. From a corpus of documents issued by the Vatican and two dioceses located in large cities (Rio de Janeiro and Rome), the research aims to deduce the values with which the Church redefined, during Holy Week, the relations of the faithful with the limits of the sacred space reconfigured in the digital. In a simulacrum of interaction, the internet user and the priest experience new spatialities, new forms of temporality and online actuality.